La patrimonialisation des grands ensembles : le quartier de l’Abreuvoir à Bobigny (Seine-Saint-Denis), œuvre d’Émile Aillaud - Jean-Bernard Cremnitzer (In Situ)
In the early 1950’s, post-war reconstruction continued with large scale public housing programmes for working classes, under the auspices of the Ministry of Reconstruction.It was in Bobigny, in Seine-Saint-Denis, that from 1950 to 1959, the city garden of the Abreuvoir was built, by the “Office public d’habitations”, the Public Office for social housing of the Seine department.The architect Émile Aillaud (1902-1988) adopted the concept of garden city, with a low density and a limited construction height, a segregation of pedestrian and vehicular traffic, and an integration of the constructions into a vast landscaped garden. The city garden forms a huge meadow into which innovative types of building have been inserted.      Since the 1960’s, the Abreuvoir neighbourhood has been suffering diverse obsolescence phenomena. An insufficient maintenance of the constructions, with insufficient ventilation of the dwellings. There is also an obsolescence of use, the small-size dwellings no longer correspond to current uses. Shops have experienced a decrease in their business activity, faced with the large-scale supermarkets located at the periphery. Finally, heritage obsolescence can be noticed, maintenance operations having failed to comply with the initial architectural and landscape principles. The urban redevelopment project currently underway (NPNRU) has been the focus of a historical and heritage study which has led to the identification of coherent urban and landscape ensembles, structured by original housing typologies, and which are organised in an ingenious way around a pedestrian mall. The General terms and conditions, called the "Masterplan patrimonial”, the Heritage Masterplan, were drawn up in a collaborative work with the project stakeholders, including the Architect of Buildings of France. This Masterplan enables the validation of the ANRU (National agency for urban renovation)’s dossier and is included in the contractor tender documentation for the project.